Application of the DMAIC cycle for cost reduction in a disposable diaper manufacturing industry - Carvalho, Pedro Eduardo Cassanti de; Miranda, Douglas (Brazilian Journal of Production Engineering, 2024)
The present work is a case study that applies DMAIC in a disposable diaper manufacturing industry with the aim of identifying waste and proposing solutions. The work was divided into five stages (Define, Measure, Analyze, Improve and Control) and initially identifies excessive consumption of two components of children's diapers. It then carries out an investigation and analysis of the production process to discover the causes of this problem, creates an action plan, carries out improvement actions and validates the effectiveness of the actions in order to reduce the environmental and financial impacts of the problem. The results show an estimated annual savings of approximately R$570,000.00, achieved without the need for investment. Finally, it creates control methods to ensure the benefits of the improvements implemented.
Keywords: six sigma; DMAIC Cycle; process improvement; cost reduction